Testing the basic socio‐structural assumptions of social identity theory in the gender context: Evidence from correlational studies on women's leadership. (18th January 2021) - Scheifele, Carolin; Ehrke, Franziska; Viladot, Maria Angels; Van Laar, Colette; Steffens, Melanie C.
Abstract: Given negative social identity, different perceptions of the structure of an intergroup relation (i.e., stability, legitimacy, permeability) should be related to different identity‐management strategies (i.e., social competition, social creativity, or individual mobility) depending on group identification. This is among the basic tenets of social identity theory (SIT). There is surprisingly little empirical support for these postulates in the context of one of the most central group identities: gender. Using a sample of women in leadership positions in Spain ( N = 649), we tested relations between structural perceptions and identity‐management strategies in a pilot study. Structural equation modeling yielded empirical support regarding social competition, but little for social creativity or individual mobility. Identity‐management strategies were related to one organizational outcome (i.e., identification with the organization). The preregistered main study is intended to replicate and extend these findings using a different sample while improving several of the measures used.